Salt and water transport in reverse osmosis thin film composite seawater desalination membranes - Zaidi, S. M. Javaid (Elsevier, 2015)
Over several decades, membrane transport has developed into established field in membrane science and technology. Two different approaches i.e., irreversible thermodynamic model (ITM) and solution diffusion model (SDM) has been thoroughly discussed in the literatures however due to its simplicity and applicability in the area of reverse osmosis desalination membrane, only SDM is chosen and discussed in this work. Recent experimental works are systematically presented for directly or indirectly validating the model.